Ecological Reading of Conflicted Self in Jewett’s “A White Heron” - Gurung, Raj Kumar (JODEM: Journal of Language and Literature, 2023)
This paper analyzes the nature-culture dichotomy as seen in the story “A White Heron” by Sarah Jewett. The main character of the story, the girl— Sylvia’s relation to nature is reflected through her contact with Mistress Moolly and birds. Her ‘self’ is torn between material greed and love for nature as she plans to tell the secret of the white heron to the hunter and her final decision not to tell the secret to save the bird respectively. When she climbs up the tree, a revelation comes to her. She reflects upon the outstanding beauty she sees in nature which was beyond her imagination. Thus, I analyze the conflicted self of Sylvia and her final take towards nature by applying environmental theories, particularly, Karen Warren’s value dualism, Val Plumwood’s backgrounding, and other relevant theories to explore nature as the major source of literature. There has not been sufficient research on this area in Nepal. This research focuses on why people are unconcerned about plants and animals. The unemployment problem and less awareness of natural heritage in man help deteriorate the entire natural environment. The concepts of community forest and being vegetarian can resolve some problems of natural environment degradation. As a qualitative paper, I use textual analysis as a tool to draw a conclusion. Then I use an analytical interpretivist approach to interpret the data.